Antennal sensilla diversity in diurnal and nocturnal fireflies (Coleoptera, Lampyridae) - Yelena M. Pacheco; Ethan Mann; Luiz, F. L. Da Silveira; Seth M. Bybee; Marc A. Branham; Joseph V. McHugh; Kathrin F. Stanger-Hall (PLoS ONE, 2025)
Insects use their antennae to collect environmental information. While the structural diversity of insect antennae is immediately obvious, the diversity of the minute antennal sensilla that interact with the environmental stimuli and translate them into sensory input, is largely unknown for many insect groups. This includes the beetle family Lampyridae, which includes nocturnal species that use bioluminescent signals during mate search, and diurnal species that rely exclusively on pheromones to identify and locate a potential mate. Relative to their bodysize, diurnal species tend to have larger antennae, and diurnal males have larger antennae than their females. It is generally assumed that antennal size reflects sensilla numbers, but this remains to be tested. We used Scanning Electron Microscopy to document the sensilla diversity of both males and females of three diurnal and four nocturnal firefly species, as well as total sensilla numbers, densities and their distribution along the antenna. We identified 14 sensilla morphotypes across the seven species, including 12 morphotypes that are new for Lampyridae. Based on their putative function we sorted all sensilla into two categories, mechanoreceptors and chemoreceptors. Mechanosensilla (3 morphotypes) were the most abundant and conserved sensilla across firefly species, and the distribution of chemosensilla (9 morphotypes) was unexpectedly variable across species. We hypothesized that the differences in mating signals between diurnal and nocturnal fireflies would be reflected in their chemosensilla counts or densities. As predicted, diurnal and nocturnal fireflies did not differ in their mechanosensilla counts or densities, nor did males and females. In contrast, firefly males had significantly more chemosensilla (and higher densities) than females and the interaction term (activity by sex) was also significant: diurnal males had significantly more chemosensilla than nocturnal males, highlighting the importance of pheromones for diurnal species. Based on a series of predictions, we also identified a pheromone sensilla candidate for each species that will facilitate functional testing in future studies.